2010
DOI: 10.2203/dose-response.10-016.iavicoli
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nanoparticles and Hormesis

Abstract: ᮀ Nanoparticles are particles with lengths that range from 1 to 100 nm. They are increasingly being manufactured and used for commercial purpose because of their novel and unique physicochemical properties. Although nanotechnology-based products are generally thought to be at a pre-competitive stage, an increasing number of products and materials are becoming commercially available. Human exposure to nanoparticles is therefore inevitable as they become more widely used and, as a result, nanotoxicology research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 53 publications
(64 reference statements)
5
103
0
Order By: Relevance
“…However, the direction of change from adaptation to a low dose that the organism can survive instead enhances resistance against the adverse effects of the same agent [97,98,[103][104][105]. Furthermore, such beneficial changes can modify responses to not only the same, but also a cross-adapted agent or stressor.…”
Section: Endogenous Amplification Phenomena In Complex Adaptive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direction of change from adaptation to a low dose that the organism can survive instead enhances resistance against the adverse effects of the same agent [97,98,[103][104][105]. Furthermore, such beneficial changes can modify responses to not only the same, but also a cross-adapted agent or stressor.…”
Section: Endogenous Amplification Phenomena In Complex Adaptive Systemsmentioning
confidence: 99%
“…More than 8,000 scientific papers have now demonstrated hormetic effects as a manifestation of biological plasticity [103]. Low doses of nanoparticles can cause hormesis [105,123]. Other studies have demonstrated that low doses of homeopathically-prepared metals, including cadmium and arsenic, can produce beneficial hormetic reversal of effects of higher, toxic doses of the same or crosssensitized agent on heat shock protein activation patterns [124].…”
Section: Organism-dependent Response Amplification Phenomenamentioning
confidence: 99%
“…Similarly, it is sufficient to note that there are potential health concerns about exposure to nanomaterials, including the possibility that nanoscale particles may pass through cell membranes, be absorbed through skin, and cross the blood brain barrier (Jordan 2010). There is currently only limited information about the health risks posed by nanomaterials, and much remains unknown about their toxicology (DHHS 2009;Iavicoli et al 2010).…”
Section: Risk Versus Benefit In Environmental Regulationmentioning
confidence: 99%
“…Nanoparticles, which are very reactive, can be toxic at relatively higher doses 25 but also elicit salutary hormetic responses at low doses. 26 The homeopathy-fibromyalgia study 1 found that the initial treatment EEG cordance response to sniffing verum homeopathic remedies distinguished patients who subsequently showed an excellent clinical response from patients who had limited clinical benefits from verum and patients who received placebo after 3 months of treatment. Olfactory administration is a less widely used, but nonetheless accepted, mode of treatment.…”
Section: Introductionmentioning
confidence: 99%